Dynamics of micro-air-vehicles with flapping wings: A multibody system approach - Roccia, Bruno Antonio (2013)
This paper presents the development of a dynamic model to study the flight mechanics of a micro-air-vehicle with flapping wings. This model is based on Lagrange's equations for constrained systems. The micro-air-vehicle is modeled as a collection of three rigid bodies a central body and two wings. The wings have prescribed motions relative to the central body, i.e., they are kinematically driven. The numerical integration of all the governing equations, which are differential-algebraic, is performed simultaneously and interactively in the time domain. The integration scheme couples a 4th-order predictor-corrector method, the modified method of Hamming, with a procedure to stabilize the resulting differential-algebraic equations.